Pertanggungjawaban Pidana terhadap Pemanfaatan Artificial Intelligence (AI) dalam Tindak Pidana Penipuan Berbasis Deepfake - Ilham Fatkul Fadjri; Aturkian Laia (INDO PUBLISHING, 2026)
The rapid development of generative artificial intelligence has introduced deepfake technology capable of producing highly realistic images, voices, and videos, creating new opportunities for fraud. This study examines the characteristics of deepfake-based fraud, analyzes criminal liability for offenders using AI, and identifies challenges in law enforcement in Indonesia. The research employs a normative legal method using statutory and conceptual approaches based on the Indonesian Criminal Code, the Electronic Information and Transactions Law, the Personal Data Protection Law, and relevant legal literature. The findings show that deepfake fraud represents a new form of conventional fraud through synthetic digital identity, creating cross-border crimes and evidentiary difficulties. Criminal liability remains attributable to human offenders who use AI as an instrument of crime. However, law enforcement faces challenges related to digital forensics, jurisdiction, and institutional capacity. Strengthening legal regulation, investigative capabilities, and adaptive criminal law policies is essential to address AI-based crimes effectively.